O Lugar Da Música Uma Análise Do Processo Criativo Sob a Perspectiva Do Receptor - RODRIGUES, Rosana Araújo (2010)
This study aims the analysis of the productive process in music considering the optics of the receiver. This analysis focuses on the history of the occidental music guided by the aesthetic theory of the perception, its conclusions and projections in the musical field. It is the analysis of the relationship between the receiver and the formal space where the music takes place in the actual and metaphoric sense in the contingencies and circumstances that surround the act of surfacing. The objective is the search of an up to date vision about the musical reception beyond the simple sensorial perception. In the process, there is a discussion about the places of music production and reception, the concepts of perception, musical linguistics, and its ways of been learned. Also, there is a debate about the process of musical structure considering the perspective and aesthetical linked to the soundscape and acoustic.